Agreement between cephalometric analyses in diagnosing the dento-skeletal characteristics of malocclusion - J. Monisha; Ulaganathan Sangeetha; Bhaskar Nivethitha; Balasubramanian Madhan (Journal of Oral Biology and Craniofacial Research)
Background: Conflicting results from different cephalometric analyses is a common problem with broader implications but has not received due attention. This study evaluated the agreement between common cephalometric analyses in diagnosing the essential dento-skeletal characteristics of malocclusion. Material and methods: A total of 125 lateral cephalograms were analyzed digitally using Downs, Steiner, Wits, Tweed, Bjork, Ricketts, and McNamara analysis. The diagnosis of sagittal jaw relation (Class 1/2/3), maxillary and mandibular positions (Orthognathic/Prognathic/Retrognathic), growth pattern (Normodivergent/Hypodivergent/Hyperdivergent), and upper and lower incisors positions (Normal/Proclined/Retroclined) were established based on each analysis. The extent of agreement between the analyses was assessed using Kappa statistics. Results: The overall agreement between analyses was moderate for sagittal jaw relationship [k = 0.41 (0.37-0.45)], fair for growth pattern [k = 0.24 (0.20-0.27)], mandibular position [k = 0.25, (0.20-0.30)], upper incisor (k = 0.38, CI = 0.32-0.44) and lower incisor [k = 0.21 (0.17-0.25)] positions, and only slight for maxillary position [k = 0.18 (0.13-0.23)]. For pairwise comparisons of analyses, the agreement was moderate to substantial for the sagittal jaw relationship (except for comparisons involving McNamara analysis) and slight to moderate for other variables. Also, the diagnosis of normal dentofacial relationships (Class 1 and normodivergent skeletal pattern, orthognathic jaw positions, and normal incisor positions) was less consistent than those of deviant subgroups. Conclusions: The agreement between the cephalometric analyses evaluated was moderate for sagittal jaw relation and only fair for most other dento-skeletal characteristics. McNamara's analysis showed less agreement with others. These highlight the need for a more cautious and scientific approach to Cephalometrics.